Differences in the Response of the Demand for Labour to Variations in Output among Canadian Regions: A Preliminary Interpretation - N.M. Swan (Queen's University, Department of Economics, 1972)
It is well known that the unemployment rate varies much more in some regions of Canada than in others. Denton has documented this for the period 1947-1964(4), and updating his data does not change the conclusions. In principle, the unemployment rate could fluctuate more in one region than another either because employment varied more around its trend or because the labour force varied more round its trend. In this paper, we focus on the proximate reasons for employment fluctuating more about its trend in some regions than in others.
Keywords: 330